From waves to rates: Enhancing inflation forecasts through combinations of frequency-domain models - Fabio Verona (Bank of Finland, 2025)
This paper addresses the challenge of inflation forecasting by adopting a thick modeling approach that integrates forecasts from time- and frequency-domain models. Frequency-domain models excel at capturing long-term trends while also accounting for short-term fluctuations. Combining these models with traditional approaches leverages their complementary strengths, resulting in forecasts that consistently outperform individual methods, especially during periods of heightened inflation volatility. By pooling insights from diverse modeling frameworks, this study provides a robust and effective strategy for improving inflation forecasts across different horizons.
urn:nbn:fi-fe202501031242
Keywords: C32; C53; E31; E37; E43; E44; 330; inflation forecasting; forecast combination; wavelets; Haar filter; time-varying parameters; Phillips curve